2012
DOI: 10.1152/physiolgenomics.00007.2012
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific mRNA expression patterns reveal a coordinated metabolic response associated with genetic selection for milk production in cows

Abstract: The molecular mechanisms regulating the physiological adaptation of tissues important for nutrient partitioning and metabolism in lactating cows are still not completely understood. The aim of our study was to identify tissue-specific regulatory mechanisms necessary to accommodate metabolic changes associated with different genetic potential for milk performance. For this purpose, we analyzed mRNA expression of genes involved in energy metabolism of segregating F(2) beef type cows with a combined genetic dairy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 74 publications
1
30
0
Order By: Relevance
“…It may result from modifications of mammary epithelium permeability, may be linked to the secretion of metabolites related to oxidative pathways in milk during early lactation (communication Pires et al, this symposium), and may constitute molecular signatures of physiological negative energy balance typical of this period. In agreement with these hypotheses, the abundance of PCK2 mRNA (a neoglugogenic gene expressed in liver) was increased in the mammary tissue of high genetic merit dairy cows (Weikard et al, 2012), and may contribute to glyceroneogenesis during fasting or compromised feed intake, as already proposed for lipogenic tissues. Introduction Improving the survival of young sheep between birth and 12 months of age is a priority for the sheep industry in Australia (Young et al 2014).…”
Section: Session 6: Feed Conversion Efficiency Towards Productivity Asupporting
confidence: 77%
“…It may result from modifications of mammary epithelium permeability, may be linked to the secretion of metabolites related to oxidative pathways in milk during early lactation (communication Pires et al, this symposium), and may constitute molecular signatures of physiological negative energy balance typical of this period. In agreement with these hypotheses, the abundance of PCK2 mRNA (a neoglugogenic gene expressed in liver) was increased in the mammary tissue of high genetic merit dairy cows (Weikard et al, 2012), and may contribute to glyceroneogenesis during fasting or compromised feed intake, as already proposed for lipogenic tissues. Introduction Improving the survival of young sheep between birth and 12 months of age is a priority for the sheep industry in Australia (Young et al 2014).…”
Section: Session 6: Feed Conversion Efficiency Towards Productivity Asupporting
confidence: 77%
“…These adaptations include metabolism adjustments in liver and peripheral tissues (including adipose tissue, mammary gland, skeletal muscle tissues and kidney), and mobilization of body reserves and increased lipid metabolism [163]. The increase in lipid metabolism results in an increase in concentrations of key metabolites NEFA and BHBA in plasma (Fig.…”
Section: Genes and Key Pathways Affecting Multiple Tissuesmentioning
confidence: 99%
“…A gene-based mapping and pathway analysis indicated that three pathways (steroid hormone biosynthesis, ether lipid metabolism and glycerophospholipid metabolism) jointly affect the concentrations of NEFA, BHBA and glucose in cows during the transition period [53]. The key genes that are involved in regulating energy metabolism in multiple tissues include PPRA, PCK1, PCK, ACACA, FASN, FBP2, FABP3, PPARGC1A, ACSL1, PPARGC1A, AGPAT6, PCCA, LPIN1, ACO, CPT-I, CPT-II and ACSL [4,15,27,94,131,163]. These genes are involved in fatty acid uptake (mainly in the liver and mammary gland), mitochondrial and peroxisomal fatty acid oxidation, ketone body metabolism (ketogenesis) and cholesterol metabolism (in liver) early in lactation in dairy cattle [135] and are discussed in the following tissue-specific sections in more detail.…”
Section: Genes and Key Pathways Affecting Multiple Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…In is well known that dairy and beef cows have been selected for different purposes and consequently, they have developed different metabolic adaptation strategies (47,51). However, to our knowledge, no studies have evaluated hepatic metabolism adaptation during gestation and early lactation in beef cows in different nutritional environments.…”
mentioning
confidence: 99%